The Interrelationships Between Marital and Housing Tenure Status of Female Adolescents and Adults in Jakarta Province - Puan Jati Megawati; Joko Adianto; Rossa Turpuk Gabe (International Journal of Built Environment and Scientific Research, 2023)
This study attempts to unveil the interrelationships between marital and housing tenure status of female adolescents and adults in Jakarta province. Although gender equality becomes one of the prioritized sustainable development goals, the housing tenure of female adolescents and adults, according to their current marital status, is rarely examined for ensuring their tenure security and improvement of well-being. The employed mixed-method research with sequential quantitative-qualitative methods delivers the crosstab analysis to identify the majority of types of housing tenure according to the marital status of 289 female respondents, and axial coding from interviews with the selected respondents to understand the interrelationship between their marital and housing status. The result highlights that life-course events such as entering marriage, parenthood, and marriage dissolution lead to housing mobility and tenure changes, which are driven by financial capacity for meeting physiological and psychological needs. It emphasizes the meaning of a house for women as a haven for physical and psychological refuge, rather than a mere representation of social status. It complements the academic conversation on the gender-related topic of housing and also enriches the housing policy, planning, and design to meet the objective of the gender equality program according to sustainable development goals.